2010
DOI: 10.2337/dc09-1392
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variation in Adiponectin and Leptin Levels and Their Association With Adiposity and Insulin Resistance

Abstract: OBJECTIVETo investigate ethnic differences in adiponectin and leptin concentration and to determine whether these adipokines and a high–glycemic index diet account for ethnic variation in insulin resistance.RESEARCH DESIGN AND METHODSIn 1,176 South Asian, Chinese, Aboriginal, and European Canadians, fasting blood samples were drawn, and clinical history and dietary habits including glycemic index/glycemic load were recorded using standardized questionnaires. Insulin resistance was defined using homeostasis mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
116
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 29 publications
(50 reference statements)
26
116
3
4
Order By: Relevance
“…44 In a Canadian study, Chinese had lower adiponectin levels than whites in both men and women after adjusting for waist circumference. 3 In our study, we found a higher degree of insulin resistance and unfavorable metabolic profiles in Malays as compared with Chinese, whereas Malays were less insulin resistant as compared with Asian Indians. Ethnic Malays represent millions of people from different Southeast Asian Island populations including Malaysians, Filipinos and Indonesians who are experiencing a rapid increase in chronic disease burden.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…44 In a Canadian study, Chinese had lower adiponectin levels than whites in both men and women after adjusting for waist circumference. 3 In our study, we found a higher degree of insulin resistance and unfavorable metabolic profiles in Malays as compared with Chinese, whereas Malays were less insulin resistant as compared with Asian Indians. Ethnic Malays represent millions of people from different Southeast Asian Island populations including Malaysians, Filipinos and Indonesians who are experiencing a rapid increase in chronic disease burden.…”
Section: Discussionsupporting
confidence: 46%
“…28 Differences in adipocyte cell size 31 and a higher ratio of total body fat to lean mass 27 have also been suggested to contribute to greater insulin resistance in Asian Indians. Furthermore, Asian Indians have been shown to have a lower adiponectin levels 3,24,26,29,30,36 and higher CRP levels 30,32,37 as compared with whites independent of BMI. In addition, dietary factors may contribute to the higher susceptibility of Asian Indians to developing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Otherwise, the strong circulating LBP reduction after fat mass loss opens new perspectives. The decrease in LBP concentration after weight loss ran in parallel with the decrease in leptin concentration, a protein produced mainly in adipocytes that circulates in proportion with body fat mass, 28 and with the decrease of complement factor B concentration, which has been reported to be expressed in human adipose tissue and adipocytes. 18 Further studies are necessary to explore these fascinating relationships.…”
Section: Discussionmentioning
confidence: 83%
“…Serum leptin (s-leptin) levels reflect the proportion of adipose tissue in the body (13), is highly correlated with fat mass (14), and correlates particularly with subcutaneous fat in women (14,15). Several studies have observed higher s-leptin levels in individuals of South Asian than European descent for the same BMI (16,17), suggesting that BMI may be a poor indicator of adiposity in South Asians. Leptin levels increase in pregnancy, due to production by the placenta, and decline rapidly after delivery (18).…”
Section: Introductionmentioning
confidence: 99%